PTU-011 Small Bowel Malignancy in Patients Undergoing Capsule Endoscopy in A Tertiary Care Academic Institution. (17th August 2016) - Johnston, C; Yung, DE; Koulaouzidis, A; Plevris, J
Abstract : Introduction: Cancer of the small-bowel (SB) is rare accounting for <5% of all gastrointestinal (GI) neoplasms. 1 Furthermore, diagnosis of SB cancer is often delayed. 2 Capsule endoscopy (CE) has become the procedure of choice for non-invasive diagnosis of SB diseases 3 . Nevertheless, data on the use of CE in diagnosis of SB cancer is limited. 4 Methods: Retrospective study; the records of all patients who underwent SBCE at our centre from Mar 2005 – Oct 2015 were reviewed; we retrieved those whose CEs were reported as suggestive of neoplasia. Further data was gathered on preceding and subsequent investigations, management and outcome of these patients. Results: From a total of 1949 CE studies (1082 PillCam TM /867 MiroCam TM ), SB neoplasia was diagnosed in 7 patients (0.36%; 2 F/5 M; median age 50, range 34–67). Two had lymphoma, 2 gastrointestinal stromal tumours (GIST), 2 duodenal adenocarcinomas, 1 jejunal metastasis from a sarcomatoid lung tumour. In these patients, CE was performed for: iron-deficiency anaemia (IDA) (n = 5), diarrhoea (n = 1) & suspicion of SB lymphoma (n = 1). 6/7 patients had prior negative bidirectional GI endoscopies; 1 had a normal gastroscopy. Prior to CE, two patients had abdominal USS, 4 had CT scan, 2 had SB follow-through and 1 had a bone marrow aspirate. Two patients had capsule retention; one was removed with a gastroscope, the other with push enteroscopy. All 7 patients had further investigations after CE. Six had a chest, abdomen & pelvis CT scan for staging. Two patients had push enteroscopy, both of whom were diagnosed with duodenal adenocarcinoma. One had double balloon enteroscopy (DBE), two had colonoscopy, two had UGIE; there was one abdominal USS and one bone marrow aspirate. Four pts underwent SB resection. Following resection, 1 patient with GIST had imatinib chemotherapy. Of the two individuals with duodenal adenocarcinoma, one underwent gastroenterostomy and the other had an elective Whipple procedure. Four patients passed away. Two remain under follow up with oncology and one with the GI team. Conclusion: SB cancers are rare and our experience is in agreement with other studies. The median age of 50 indicates that SB malignancy is more common in relatively younger patients. Unexplained iron deficiency anaemia was the main presenting complaint in our patients which triggered further investigation despite negative bidirectional endoscopies. CE is effective in picking up SB neoplasia where other imaging modalities have failed. References: 1 Schottenfeld D, Beebe-Dimmer JL, Vigneau FD. The epidemiology and pathogenesis of neoplasia in the small intestine. Ann Epidemiol 2009;19 :58–69. 2 Pennazio M, Rondonotti E, de Franchis R. Capsule endoscopy in neoplastic diseases. World J Gastroenterol 2008;14 :5245–53. 3 Pennazio M, Spada C, Eliakim R, et al . Small-bowel capsule endoscopy and device-assisted enteroscopy for diagnosis and treatment of small-bowel disorders: European Society of Gastrointestinal Endoscopy (ESGE) Clinical Guideline. Endoscopy 2015;47 :352–86. 4 Rondonotti E, Pennazio M, Toth E, et al . Small-bowel neoplasms in patients undergoing video capsule endoscopy: a multicenter European study. Endoscopy 2008;40 :488–95. Disclosure of Interest: C. Johnston: None Declared, D. Yung: None Declared, A. Koulaouzidis Grant/research support from: ESGE- Given®Imaging Research grant 2011, J. Plevris: None Declared